FRI0610 Ultrasonograpic Assessment Covers a Pitfal of Physycal Examination in the Ankle Joints in Patients with Rheumatoid Arthritis. (9th June 2015) - Toyota, Y.; Minegishi, K.; Hama, M.; Yoshimi, R.; Sugiyama, Y.; Tsuchida, N.; Kunishita, Y.; Kishimoto, D.; Kamiyama, R.; Kirino, Y.; Takeno, M.; Ueda, A.; et al.
Abstract : Background: Though rheumatoid arthritis (RA) commonly affects feet and ankles, precise clinical evaluation for ankle is difficult because of its complex anatomy and deformity as well as other various factors such as obesity and edema. Objectives: To clarify the utility of ultrasonography (US) examination for evaluating RA ankle by means of comparison to physical examination. Methods: This study included 56 RA patients (women 82%, age 62±15 y.o., disease duration 7.2±8.2 years, DAS28-ESR 3.95±1.65). Physical examination and patient's visual analogue scale (VAS) for pain of each bilateral ankle were evaluated. Clinical ankle involvement was defined as ankle joint swelling and/or tenderness on physical examination. Bilateral tibiotalar joints and three tendon sites (anterior tendons; tibialis anterior, extensor hallucis longi, extensor digitorum longi, medial tendons; tibialis posterior, flexor digitorum longi, flexor hallucis longi, lateral tendons; peroneus longi and brevis) were assessed by gray scale (GS) and power Doppler (PD) US examination. Intraarticular synovitis (synovitis) and tenosynovitis were separately assessed by semiquantitative scoring (0-3). Positive US findings were defined as a GS score ≥2 and/or a PD score ≥1. Results: Among a total of 112 ankle joints, 28 (25.0%) were clinically swollen and 19 (17.0%) had tenderness. US examination showed that synovitis existed in 17 ankles (19.1%) of all the tibiotalar joints, whereas 23 (20.5%) had tenosynovitis of at least one site among three tendon sites. Tenosynovitis lesions of any tendon in a site were detected at 5 (4.5%) of all the anterior sites, 14 (12.5%) of medial sites, and 13 (11.6%) of lateral sites, respectively. When comparing clinical assessments among 4 groups divided according to the existence of synovitis and tenosynovitis (Table ), patient's VAS of ankle is the highest in the group of ankles affected by both synovitis and tenosynovitis. Positive physical findings (swollen and/or tender) were more highly concordant with tenosynovitis (κ =0.64) than synovitis (κ =0.32), and were also more closely associated with tenosynovitis than in synovitis. When positive US findings were set as the gold standard, sensitivity and specificity of positive physical findings (swollen and/or tender) were 0.56 and 0.81 for synovitis, and 0.73 and 0.87 for tenosynovitis, respectively. Conclusions: This study shows that physical examinations of the ankles often reflect tenosynovitis rather than intraarticular synovitis. US sensitively illustrate RA involvement in the ankle joints, particularly intraarticular lesions, which are often overlooked by physical examination. Disclosure of Interest: None declared